Unlocking the potential of electric vehicles to enhance large-scale photovoltaic solar energy integration into grid systems - a case for Saudi Arabia - Alotaibi, Saleh (2023)
Traditionally, the Kingdom of Saudi Arabia (KSA) has relied heavily on fossil fuels to meet its energy demands. However, due to environmental concerns and economic incentives, the Kingdom is planning to escalate renewable energy generation, notably from Solar Photovoltaic (PV), and to promote the widespread adoption of electric vehicles (EVs). One of the issues associated with solar energy is its intermittent nature, and its large-scale integration could pose a challenge to the grid system; therefore strategies to alleviate this problem are required. This thesis investigates the potential of EVs to support the country’s renewable energy aspirations by enhancing large-scale PV energy integration into the Saudi grid. This study begins by considering the current energy situation in KSA, the development of solar PV in the country, and the challenges associated with large-scale solar PV integration into the grid. It then reviews the state-of-the-art in EVs, their related charging infrastructure, and Vehicle-to-Grid (V2G) technology, which enables EVs to feed energy back to the grid when demand is high. This is a particularly useful feature in the Saudi context, where demand for electricity fluctuates heavily between summers and winters (and between day-time and night-time) due to the need for air conditioning during the excessive summer heat. The study goes on to explore the current status of EVs in Saudi Arabia and the factors that are most likely to affect their widespread adoption in the country. It finds that battery-driven electric vehicles (BEVs) are more likely to find acceptance than other EV types in KSA due to their zero emissions, better safety levels, and the fact that owners can benefit financially by exporting their excess energy via V2G. The study then considers the opinions of Saudi citizens to determine the factors and features that they deem important in EVs, which were gathered via a survey conducted for this purpose. Responses from 1012 potential EV drivers were analysed in order to identify and rank their preferences, leading to the identification of the features most likely to influence Saudi citizens’ adoption of EVs. The main barriers identified related to infrastructure, performance, financial, social, and policy, but the most important were the lack of charging infrastructure and the additional load placed on the grid. Concerns about the safety and performance of EV batteries in high temperatures and EVs ability to perform in desert conditions emerged as novel concerns related to the Saudi context. These findings were validated in a workshop conducted by the Saudi Standards, Metrology, and Quality Organization (SASO) via a focus group of EV users who shared their experience of using EVs in KSA. Their responses were in line with the earlier survey, and three major themes emerged related to EV infrastructure, battery performance, and lack of effective policy. The study then assesses the viability of implementing a solar-powered system to support EVs in major Saudi cities. After analysing several cities in terms of their potential to generate electricity using solar PV and expected increases in the numbers of EVs by 2030, Riyadh was identified as the most suitable location for a case study to test the viability of three models through simulation. These included Model 1 (PV Plant Only), Model 2 (PV Plant and Charging Stations), and Model 3 (PV, Charging Stations and V2G). Techno-economic analysis of these models in low, medium and high EV uptake scenarios (LUS, MUS and HUS) revealed that Model 1 (PV Only) would be the cheapest option at around $1 billion in LUS. However, Model 3 (PV plant, charging stations and V2G) has the best Internal Rate of Return (IRR) (around 28.2% in HUS) and would reduce emissions most significantly (by around 5.5 mtCO2 in HUS). The study concludes that EVs have considerable potential to enhance large-scale PV energy integration into the Saudi grid and proposes the construction of solar PV plants together with charging stations and V2G technology as a cost-effective alternative to PV plants alone. It also recommends that EV manufacturers demonstrate that their vehicles are safe and effective in hot desert climates if they wish to penetrate the Saudi market. In order to promote a widespread EV implementation, the government and all other authorities should develop policies to support EV adoption, including by providing subsidies or other incentives to EV users. The data gathered for this study and the research findings will be of interest to policymakers, EV manufacturers, entities charged with providing EV infrastructure, solar PV and EV businesses, and any sector working towards the Vision 2030 goals